The Investigation of the Research on Out-of-School Learning Activities in Turkey: A Systematic Review - Mustafa Metin; Emir Oker; Aslı Saylan Kirmizigül (Journal of Science Learning, 2022)
This research aims to analyze the studies on out-of-school learning activities in Turkey between 2000 and 2020. For this purpose, 303 studies were selected, of which 211 articles, 73 master's thesis, and 19 doctoral dissertations, with the phrase "out-of-school learning" in the title and keywords. A systematic literature review was conducted in the research. The data were entered into the Content Analysis Monitoring Form, and the analyses were made on the Microsoft Excel program. In line with the findings obtained, it was determined that most of the studies on out-of-school learning activities were carried out in 2020. In these studies, it was seen that it was mainly aimed to determine the opinions of teachers or students about out-of-school learning activities, the sample was selected in the range of 21-40 people, and the most selected sample group was secondary school students. It was also determined that the studies were mostly done in the science discipline and that the case study from qualitative and experimental research design from quantitative methods was used. When all the findings were evaluated, since there are not many studies on the effect of out-of-school learning activities on anxiety, motivation, and interest, it is recommended to carry out studies in this area and to increase the studies to be done towards high school, preschool, primary school students.